The Double Dividend of Attention-Releasing Policies - Steffen Altmann; Andreas Grunewald; Jonas Radbruch (Center for Economic Studies and ifo Institute (CESifo), 2024)
We study the effects of two widely observed behavioral policy interventions⸻the simplification of complex decisions and the implementation of high-quality defaults. Based on a laboratory experiment featuring a dual-task paradigm, we demonstrate that these policies do not only improve decisions in the targeted choice domain, but also yield substantial positive indirect effects on non-targeted decisions. The latter emerge as a result of an attention-releasing effect of the policies. Furthermore, the relative importance of the direct and indirect effects varies systematically across the population. Evaluations that focus only on the targeted domain may therefore significantly underestimate the overall effectiveness of attention-releasing policies and provide a biased assessment of their distributional consequences.
Keywords: D91; D01; D04; C91; 330; administrative burden; limited attention; defaults; nudges; limited cognitive resources; behavioral economics; laboratory experiment